Changes in religious tourism in Poland at the beginning of the 21st century - Mróz, Franciszek (Turyzm/Tourism, 2019)
This study presents changes in religious tourism in Poland at the beginning of the 21st century. These include the development of a network of pilgrimage centers, the renaissance of medieval pilgrim routes, the unflagging popularity of pilgrimages on foot as well as new forms using bicycles, canoes, skis, scooters, rollerblades and trailskates; along with riding, Nordic walking, running and so on. Related to pilgrimages, there is a growing interest in so-called ‘holidays’ in monasteries, hermitages and retreat homes, as well as a steady increase in weekend religious tourism. Religious tourists and pilgrims are attracted to shrines by mysteries, church fairs and religious festivals, in addition to regular religious services and ceremonies.